Pengaruh Kepemimpinan dan Penerapan Disiplin Kerja terhadap Kinerja Karyawan di Industri Hiburan - Fri May Dini Silalahi; Sari Suswati (BADAN PENERBIT STIEPARI PRESS, 2022)
Employee performance is a crucial element in the highly competitive entertainment industry, where service quality and innovation play an important role in maintaining competitive advantage. This research explores the influence of leadership and the application of work discipline on employee performance in the entertainment industry, focusing on how these two factors interact to influence workforce effectiveness and productivity. Through a quantitative approach, data was collected from a survey involving 200 employees from various entertainment companies, including film studios, music companies, and theaters. The results showed that effective leadership, characterized by good communication, transparent decision-making, and motivational support, has a significant positive influence on employee performance. In addition, consistent and fair application of work discipline, which includes adherence to operational rules and standards, also contributes significantly to improved employee performance. These findings provide valuable insights for managers in the entertainment industry to design more effective managerial strategies to improve employee productivity and satisfaction, and achieve sustainable competitive advantage.